1998
DOI: 10.1080/000368498324977
|View full text |Cite
|
Sign up to set email alerts
|

The causes and consequences of occupational segregation: a simultaneous equations approach

Abstract: Lewis and Shorten (Applied Economics, 1991, 23, 167-77) have proposed that male and female earnings, male and female labour force participation rates and occupational segregation are simultaneously determined in the labour market. They estimate their model for Australia using 1981 Census data and find substantial evidence to support their hypothesis. However, there have been no subsequent studies to empirically test their hypothesis for other countries. In this paper their model for the United States using 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Although occupational segregation by gender could reflect efficiency reasons and individual preferences, it is also responsible for a large part of the gender wage gap because women are overrepresented in lower paying occupations (cf. Fain, 1998;Reed and Dahlquist, 1994;Jurajda and Harmgart, 2003). Moreover, there are fewer career opportunities in female occupations than in male occupations (Jacobsen, 1998).…”
Section: Human Capital Depreciation During Hometime 1 Introductionmentioning
confidence: 99%
“…Although occupational segregation by gender could reflect efficiency reasons and individual preferences, it is also responsible for a large part of the gender wage gap because women are overrepresented in lower paying occupations (cf. Fain, 1998;Reed and Dahlquist, 1994;Jurajda and Harmgart, 2003). Moreover, there are fewer career opportunities in female occupations than in male occupations (Jacobsen, 1998).…”
Section: Human Capital Depreciation During Hometime 1 Introductionmentioning
confidence: 99%
“…The third explanation relates to market segregation and different occupational preferences (Castellano and Rocca, 2020;Fain, 1998;Garc ıa-Aracil, 2007;G€ orlich and de Grip, 2009;Leuze and Strauß, 2016;Murphy and Oesch, 2016;Reed and Dahlquist, 1994;Sloane et al, 2019;Triventi, 2013). Two types of segregation can be identified: horizontal and vertical.…”
Section: Theoretical Approaches and Their Empirical Applications To T...mentioning
confidence: 99%
“…Many authors have suggested that women are willing to accept lower wages in exchange for job characteristics such as flexible work schedules or the ability to combine work with childcare (Fain 1998; see also Polachek 1981;Filer 1985). If this tendency is the case, much of what is labeled as occupational segregation is, in fact, women's voluntary choice.…”
Section: Labor Markets Firm Productivity and Gendermentioning
confidence: 99%